Inorganic filler reinforced elastomer toughened high-strength polypropylene composite material and preparation method thereof

By inducing dynamic crosslinking in the rubber dispersed phase by surface modified nanoparticles, the problem of difficult balance of strength and toughness of existing PP toughening materials is solved, and the strength balance of PP composite materials is achieved and the preparation process is simplified.

CN119613859APending Publication Date: 2025-03-14TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411678970.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The strength of existing PP toughening materials is significantly reduced when improving toughness, and the preparation process is complicated and the yield is poor, making it difficult to achieve strong balance.

Method used

The surface-modified nanoparticles have better dispersion in the rubber dispersed phase and trigger dynamic crosslinking of the rubber dispersed phase, making the rubber dispersed phase structural network more perfect, increasing the propagation ability of impact energy, and improving the fixity of particle positions, providing a stress concentration point for the dissipation of impact energy.

Benefits of technology

The strength and toughness balance of PP composite materials is achieved, the toughness and strength of composite materials are improved, and the preparation process is simplified, the cost is reduced, and the yield is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613859A_ABST
    Figure CN119613859A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, in particular to an inorganic filler reinforced elastomer toughened high-strength polypropylene composite material and a preparation method thereof. Comprising the following components in percentage by weight: 50-75% of polypropylene, 20-40% of a rubber elastomer, 0.5-20% of organic modified inorganic particles, 0-0.1% of a beta nucleating agent and 0.5-3% of an antioxidant. The preparation method comprises the following steps: S1, putting the organically modified inorganic particles and the rubber elastomer into an internal mixer to prepare the composite rubber. S2, putting the composite rubber obtained in the step S1 and polypropylene into an internal mixer, adding a beta nucleating agent and an antioxidant, and blending to obtain the polypropylene composite material. The yield strength of the PP composite material is improved while effective toughening is achieved, and toughness balance of the PP composite material is achieved. And meanwhile, compared with other block elastomer fillers, the cost is lower, the material structure requirement is lower than the formation requirement of core-shell particles, the material preparation process is simple, and the yield is higher.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a high-strength polypropylene composite material reinforced with an inorganic filler and toughened with an elastomer, and a preparation method thereof. Background Art

[0002] Polypropylene (PP) is a semi-crystalline thermoplastic polymer with good thermal properties, low price, and excellent chemical resistance. It is one of the most widely used thermoplastics. However, the poor toughness and notch sensitivity of pure PP materials prevent it from becoming an excellent engineering plastic, limiting its application areas.

[0003] Toughening PP materials by physical blending is the most widely used method in the actual production process of PP materials. At present, common physical toughening schemes include: elastomer toughening, rigid particle toughening and core-shell particle toughening.

[0004] The Chinese invention patent, publication number CN118290860A, discloses an EPDM / PP thermoplastic elastomer composition and a thermoplastic elastomer material and its preparation method and application, wherein EPDM / PP composite plastic is obtained by toughening polypropylene with EPDM. However, due to the low strength of the rubber elastomer itself, the toughened PP composite material has a significantly reduced strength while the toughness is improved, and the tensile strength of the prepared EPDM / PP composite material is only 8.9MPa.

[0005] Chinese invention patent, publication number CN117264333A discloses an EPDM / silicone rubber / polypropylene thermoplastic elastomer and preparation method, wherein EPDM and silicone rubber are used to toughen PP to obtain a PP composite material. However, due to the low strength of the rubber elastomer itself, the toughened PP composite material has improved toughness but significantly reduced strength, and the tensile strength of the prepared composite material is about 15 MPa.

[0006] Rigid particle toughening is another physical method for PP toughening. The inorganic particles themselves have a high modulus and can effectively alleviate the problem of strength loss in PP composites. However, the inorganic particles themselves cannot effectively transmit impact energy, so the toughness improvement of PP composites is limited.

[0007] China invention patent, publication number CN114539812A discloses an inorganic powder and its preparation method, a reinforced toughened polypropylene modified masterbatch, and physically blends nano-silicon dioxide slurry, wollastonite micropowder slurry and PP to obtain an inorganic particle toughened PP composite material. Its impact strength is only 7.2KJ / m 2 .

[0008] At present, the most researched topic is toughening of core-shell particles. A Chinese invention patent, publication number CN117511058A, discloses a polyolefin elastomer and its application, using a softer branched polypropylene as a core and a harder cross-linked polymer as a shell to prepare a core-shell dispersed phase to toughen PP.

[0009] Chinese invention patent, publication number CN118290856A discloses a low-gloss high-impact modified polypropylene composite material and its preparation method, using a softer end-hydroxyl ASA-PP as a shell and a harder silica particle as a core-shell dispersed phase to physically toughen PP. The resulting PP composite material has higher strength and toughness than a single elastomer toughened PP composite material. However, the core-shell particle dispersed phase molding requirements of this toughening method are relatively strict, such as a polyolefin elastomer and its application disclosed in Chinese invention patent, publication number CN117511058A and a low-gloss high-impact modified polypropylene composite material and its preparation method disclosed in Chinese invention patent, publication number CN118290856A. In order to ensure the molding of the core-shell particle structure, a very complex preparation process and preparation technology are used. Once the core-shell particle structure is incomplete, the strength of the composite material will drop significantly.

[0010] In summary, toughening PP with a single elastomer or with rigid particles cannot solve the problem of balancing strength and toughness. High toughness means low strength, and high strength means low toughness. Toughening PP materials with a combination of multiple composite rubbers and elastomers has alleviated the problem of strength decline of PP materials toughened with a single elastomer to a certain extent, but the material strength is still insufficient. At the same time, the toughening method of composite rubber elastomers with excellent toughening effect generally requires the addition of some block polymer elastomers with high preparation costs, which is not conducive to large-scale production and promotion.

[0011] PP is toughened by constructing a dispersed phase of core-shell particles. Although the strength and toughness are improved compared with the above toughening methods, the conditions for the formation of core-shell particles are relatively strict and the material yield is poor. If the core-shell structure formed during the synthesis process is not perfect, the strength and toughness of the PP composite material will be greatly reduced.

[0012] Therefore, there is an urgent need to improve the existing PP toughening formula and preparation method, so as to achieve a balance of strength and toughness of the prepared PP composite materials on the basis of low cost, simple preparation method and higher yield. Summary of the invention

[0013] In order to solve the deficiencies in the prior art, the present invention provides a high-strength polypropylene composite material reinforced with an inorganic filler and toughened with an elastomer and a preparation method thereof. The purpose of the present invention is to solve the problem that the strength and toughness performance of the existing PP toughening materials are difficult to balance, and to provide a method for preparing a strong and tough balanced PP composite material using surface modified nanoparticles. The method provided by the present invention enables the surface modified nanoparticles to have a better dispersed phase in the rubber dispersed phase, and triggers the dynamic crosslinking of the rubber dispersed phase, so that the structural network of the rubber dispersed phase is more perfect, and the morphology of the rubber dispersed phase gradually evolves from an ellipsoid to a long strip stretch, which is more conducive to the propagation of impact energy, and at the same time fixes the particle position, providing a stress concentration point for the dissipation of impact energy, thereby greatly improving the toughness of the composite material. At the same time, the method provided by the present invention allows particles with a higher modulus to equivalently replace part of the rubber dispersed phase of the same volume, and at the same time, dynamic crosslinking increases the modulus of the rubber dispersed phase itself, so that the modulus of the PP composite material is greatly improved compared with the elastomer toughened composite material, and the prepared PP composite material has both good strength and toughness.

[0014] The technical solution of the present invention is:

[0015] An inorganic filler reinforced elastomer toughened high-strength polypropylene composite material comprises the following components in weight percentage: 50-75% polypropylene, 20-40% rubber elastomer, 0.5-20% organic modified inorganic particles, 0-0.1% beta nucleating agent, and 0.5-3% antioxidant.

[0016] As a preferred embodiment of the composite material of the present invention, the polypropylene is any one of isotactic copolymer polypropylene (IPP), random copolymer polypropylene (PPR), and high-density polypropylene (HPP). As a further preferred embodiment, the polypropylene is isotactic copolymer polypropylene (IPP).

[0017] As a preferred embodiment of the composite material of the present invention, the rubber elastic body is at least one of ethylene propylene diene rubber (EPR), ethylene propylene diene rubber (EPDM), styrene-butadiene-styrene block copolymer (SBS), hydrogenated styrene-butadiene block copolymer (SEBS), ethylene-octene copolymer (POE), ethylene-octene block copolymer (OBC), and styrene-ethylene-propylene-styrene block copolymer (SEPS). As a further preferred embodiment, the rubber elastic body is ethylene propylene diene rubber (EPDM).

[0018] As a preferred embodiment of the composite material of the present invention, the organically modified inorganic particles are at least one of spherical silica, halloysite, silica aerogel, and rod-shaped silica. As a further preferred embodiment, the organically modified inorganic particles are spherical silica.

[0019] As a preferred embodiment of the composite material of the present invention, the method for preparing the organically modified inorganic particles comprises the following steps:

[0020] S1. Dissolve the silane coupling agent in an organic solvent to prepare a modifier solution.

[0021] S2. Place the inorganic particles in a high temperature mixer and dehydrate at 100-150° C. and 200-500 rpm for 20-50 min.

[0022] S3. Spray the modifier solution prepared in S1 into the high-temperature mixer in S2 in 5-10 times. After each spraying, continue stirring at 100-150° C. and 200-500 rpm for 3-5 minutes. After all spraying is completed, continue stirring for 20-50 minutes.

[0023] As a preferred embodiment of the composite material of the present invention, the silane coupling agent is at least one of 3-(2,3-epoxypropyloxy)propyltrimethoxysilane (KH560), 3-(2,3-epoxypropyloxy)propyltriethoxysilane (KH561), 3-(2,3-epoxypropyloxy)propylmethyldiethoxysilane (KH563), 3-(3,4-epoxycyclohexyl)trimethoxysilane (A186), 3-aminopropyltriethoxysilane (KH550), methyltrimethoxysilane, phenyltrimethoxysilane, and bis-[γ-(triethoxysilyl)propyl]tetrasulfide (Si-69). As a further preferred embodiment, the silane coupling agent is bis-[γ-(triethoxysilyl)propyl]tetrasulfide (Si-69).

[0024] As a preferred embodiment of the composite material of the present invention, in the method for preparing the organically modified inorganic particles, the organic solvent is a 50-100% ethanol aqueous solution, preferably a 90% ethanol aqueous solution.

[0025] As a preferred embodiment of the composite material of the present invention, in the method for preparing the organically modified inorganic particles, the concentration of the silane coupling agent in the modifier solution is 1-20 g / ml.

[0026] As a preferred embodiment of the composite material of the present invention, in the method for preparing the organically modified inorganic particles, the inorganic particles are spherical silica, and the mass ratio of the spherical silica particles to the silane coupling agent is 100:(1-10).

[0027] As a preferred embodiment of the composite material of the present invention, the β-nucleating agent is at least one of calcium carbonate, aluminum oxide, anthracene, naphthalene, 2-mercaptobenzimidazole, N,N'-dicycloethylterephthalamide, and TMB-5. Preferably, TMB-5.

[0028] As a preferred embodiment of the composite material of the present invention, the antioxidant is at least one of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol ester (antioxidant 1010), N-isopropyl-N'-phenyl-p-phenylenediamine (4010NA), 2,2,4-trimethyl-1,2-dihydroquinoline polymer (RD), and 2-mercaptobenzimidazole (MB). Preferably, tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol ester (antioxidant 1010) is used.

[0029] The present invention also provides a method for preparing a high-strength polypropylene composite material reinforced with an inorganic filler and toughened with an elastomer, comprising the following steps:

[0030] S1. Place the organically modified inorganic particles and the rubber elastomer into an internal mixer, and fully blend them at 90-110° C. and 50-80 rpm for 10-15 min to obtain a composite rubber.

[0031] S2. Put the composite rubber and polypropylene obtained in S1 into an internal mixer, add a β-nucleating agent and an antioxidant, and fully blend at 180-210° C. and 50-80 rpm for 8-12 minutes to obtain a polypropylene composite material.

[0032] The beneficial effects achieved by the present invention are:

[0033] 1. Compared with the elastomer toughening method that has a huge loss of strength during the toughening process, the present invention improves the yield strength of the PP composite material while effectively toughening it, achieving a strong-tough balance of the PP composite material. The strength and toughness of the PP composite material are effectively improved. At the same time, compared with other block elastomer fillers, the cost is lower, the material structure requirements are lower than the formation requirements of core-shell particles, the material preparation process is simple, and the yield rate is higher.

[0034] 2. The method provided by the present invention makes the surface modified nanoparticles have better dispersibility in the rubber dispersed phase, and triggers the dynamic crosslinking of the rubber dispersed phase, making the rubber dispersed phase structure network more perfect, and the morphology of the rubber dispersed phase gradually evolves from ellipsoidal to long strips, which is more conducive to the propagation of impact energy. At the same time, the particle position is fixed, providing a stress concentration point for the dissipation of impact energy, thereby greatly improving the toughness of the composite material. At the same time, the method provided by the present invention allows particles with higher modulus to equivalently replace part of the rubber dispersed phase of the same volume. At the same time, dynamic crosslinking increases the modulus of the rubber dispersed phase itself, so that the modulus of the PP composite material is greatly improved compared with the elastomer toughened composite material, and the prepared PP composite material has both good strength and toughness. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1It is a graph showing the impact strength test results of the PP composite materials obtained in Comparative Examples 1 to 2 and Examples 3 to 6 of the present invention.

[0036] Figure 2 The tensile modulus and tensile yield diagram of the PP composite materials obtained in Comparative Examples 1 to 2 and Examples 3 to 6 of the present invention are shown.

[0037] Figure 3 A1 Scanning electron microscope image (500x) of the PP composite material obtained in Comparative Example 1.

[0038] Figure 3 B1 Scanning electron microscope image (500x) of the PP composite material obtained in Comparative Example 2.

[0039] Figure 3 C1 Scanning electron microscope image (500x) of the PP composite material obtained in Example 4.

[0040] Figure 3 D1 Scanning electron microscope image (500x) of the PP composite material obtained in Example 5.

[0041] Figure 3 E1 Scanning electron microscope image (500x) of the PP composite material obtained in Example 6.

[0042] Figure 4 A2 Scanning electron microscope image (10K) of the PP composite material obtained in Comparative Example 1.

[0043] Figure 4 B2 Scanning electron microscope image (10K) of the PP composite material obtained in Comparative Example 2.

[0044] Figure 4 C2 Scanning electron microscope image (10K) of the PP composite material obtained in Example 4.

[0045] Figure 4 D2 Scanning electron microscope image (10K) of the PP composite material obtained in Example 5.

[0046] Figure 4 E2 Scanning electron microscope image (10K) of the PP composite material obtained in Example 6.

[0047] Figure 5 A Transmission electron microscopy (30kx) of the PP composite material obtained in Comparative Example 2.

[0048] Figure 5 B is the transmission electron microscopy (30kx) of the PP composite material obtained in Example 6.

[0049] Figure 6 A Transmission electron microscopy (50kx) of the PP composite material obtained in Comparative Example 2.

[0050] Figure 6 B is the transmission electron microscopy (50kx) of the PP composite material obtained in Example 6. DETAILED DESCRIPTION

[0051] To facilitate those skilled in the art to understand the present invention, specific implementations of the present invention are described below with reference to the accompanying drawings.

[0052] The raw materials and manufacturers used in the present invention are as follows:

[0053] 15 nm silica nanoparticles were purchased from Beijing Mairida Technology Co., Ltd.

[0054] Si69 was purchased from Nanjing Nengde New Material Technology Co., Ltd.

[0055] EPDM rubber (4045M) was purchased from Sinopec Mitsui Branch.

[0056] Antioxidant 1010 was purchased from Beijing Jiyi Holding Company.

[0057] TMB-5 was purchased from Shanxi Fine Chemical Research Institute.

[0058] IPP (T30S) was purchased from Qingyang Petrochemical Company of China National Petroleum Corporation.

[0059] Examples 1 and 2 provide a specific preparation method for surface-modified nanoparticles. The raw materials and proportions used are shown in Table 1. The specific preparation method is as follows:

[0060] 1) The silane coupling agent was dissolved in a 90 wt % ethanol aqueous solution to prepare modifier solutions of different concentrations.

[0061] 2) Place 200 g of 15 nm spherical silica in a high-speed stirrer and stir at 120° C. and 300 rpm for 30 min.

[0062] 3) The modifier solution prepared in step 1) was sprayed into the high-speed mixer in 10 times in the form of spray. After each spraying, high-speed stirring was continued for 5 minutes under the conditions in step 2). After all the spraying was completed, high-speed stirring was continued for 30 minutes.

[0063] 4) After the high-temperature stirring is completed, the high-speed stirrer is opened and left for 1 hour to allow the organic solvent to continue to evaporate.

[0064] Table 1 Ratio of components for surface modification of silica particles

[0065]

[0066] Examples 3 to 6 and Comparative Examples 1 to 2 provide a PP composite toughening material and a preparation method thereof. The components and proportions used in the PP composite material are shown in Table 2. The specific preparation method is as follows.

[0067] (1) The modified silica particles prepared in Example 2 and EPDM (a total of 200 g) were placed in a Haake internal mixer and fully blended at 100° C. and 80 rpm for 15 min to obtain a composite rubber.

[0068] (2) The composite rubber prepared in step (1) and PP (240 g in total) were placed in a Haake internal mixer at a mass ratio of 30:70, and 2 wt% of antioxidant 1010 and 0.01 wt% of β-nucleating agent TMB-5 were added. The mixture was fully blended at 195° C. and 80 rpm for 8 min to prepare a PP composite material.

[0069] Table 2 Components and dosage of PP composites prepared from surface modified particles

[0070]

[0071] The PP composite materials obtained in the above comparative examples 1 to 2 and embodiments 3 to 6 were subjected to notched impact test experiments at different temperatures according to GB / T 1043.2-2018. The test temperatures were 25°C, 10°C, 0°C, and -10°C. The obtained impact strength test results are as follows: Figure 1 shown.

[0072] The PP composite materials obtained in the above comparative examples 1 to 2 and examples 3 to 6 were subjected to room temperature tensile tests according to GB / T1040.1-2018, and the tensile modulus and tensile yield strength were obtained. Figure 2 .

[0073] from Figure 1 and Figure 2 It can be seen from the mechanical properties of the prepared PP composite materials in the comparison that the room temperature toughness of the PP composite materials prepared in Examples 3 to 6 gradually increases with the increase in the content of surface-modified silica particles, especially in Examples 3, 5, and 6, the toughness far exceeds that of Comparative Example 1 and Comparative Example 2. At the same time, the tensile yield strength and tensile modulus of Examples 3 to 6 are also significantly improved compared with Comparative Example 1 and Comparative Example 2.

[0074] In order to study the reasons for the improved performance of Examples 3 to 6, scanning electron microscope observation was performed on Comparative Examples 1 to 2 and Examples 4 to 6. The images obtained are as follows: Figure 3 As shown in A1~4E2.

[0075] The PP composite materials obtained in Example 2 and Example 6 were observed by transmission electron microscopy, and the images obtained are as follows: Figure 5 As shown in A-6B.

[0076] Depend on Figure 3It can be seen from the morphology of the rubber dispersed phase of the PP composite materials shown in A1~4E2 that, when the proportion of the matrix remains unchanged, the rubber dispersed phase of the single rubber elastomer toughened PP composite material in Comparative Example 1 is spherical or ellipsoidal, while in Comparative Example 2, the addition of unmodified inorganic spherical silica does not change the morphology of the dispersed phase in the composite material, and the particles are prone to agglomeration in the dispersed phase, which is not conducive to the propagation of impact energy. Therefore, the unmodified particles fail to improve the toughness and strength of the PP composite material.

[0077] The reason for the increase in toughness in Examples 4, 5, and 6 is that the surface-modified silica particles containing -SS- bonds allow dynamic crosslinking between the rubber dispersed phase EPDM containing double bonds, making the network structure of the rubber dispersed phase more perfect, and changing the distribution morphology of the rubber dispersed phase in the PP matrix, so that the dispersed phase gradually stretches from an ellipsoid to a strip shape, and the particles are fixed in the rubber dispersed phase and fully dispersed and not easy to agglomerate. As a rubber equivalent volume filler, it provides a stress concentration point for the dissipation of impact energy during the impact process, greatly improving the toughness of the composite material. At the same time, the addition of surface-modified particles also greatly improves the elastic modulus and tensile yield stress of Examples 4 to 6 compared with the comparative example. This is because the particles used as rubber equivalent volume fillers themselves have a higher modulus, and the dynamic crosslinking process in the dispersed phase also increases the strength of the rubber itself, increasing the strength of the PP composite material.

[0078] At the same time, in order to regulate the mechanical properties of the PP composite material and prove the influence of the dispersed phase on the mechanical properties of the PP composite material, Example 3 reduces the content of the PP matrix and simultaneously increases the content of the dispersed phase. Compared with Example 5, the particle and rubber contents of Example 3 are increased. The increase in the dispersed phase enables Example 3 to obtain higher strength and toughness than Example 5. Compared with Example 6, the particle content of Example 3 remains unchanged, and the rubber content increases. This reduces the room temperature toughness of Example 3, but obtains higher low-temperature toughness. This further proves the influence of the cross-linked rubber dispersed phase on the strength-toughness balance of the PP composite material, and shows that the rubber contributes more to the toughness at low temperatures. Compared with the comparative example, Examples 3, 5, and 6 achieve the strength-toughness balance of the PP composite material.

[0079] Nano-spherical silica (SiO 2) is a filler that can effectively toughen PP composite materials. Compared with other block polymers or fillers with excellent toughening effects, it has a simple preparation process and low manufacturing cost. However, as shown in Comparative Example 2, conventional nano-silicon dioxide has a large number of hydrogen bonds on its surface, is not easy to disperse in an organic polymer matrix, and is easy to agglomerate between particles, which deteriorates the performance of the composite material and is not conducive to its promotion and use. The present invention effectively improves the problem of a significant decrease in the strength of the PP material due to the addition of the elastomer in the process of toughening the PP material with the elastomer by surface modifying the spherical silicon dioxide particles and adding the surface-modified particles to the PP composite material.

[0080] The purpose of the present invention is to solve the problem that the strength and toughness performance of existing PP toughening materials are difficult to balance, and to provide a method for preparing a strong and tough balanced PP composite material using surface modified nanoparticles. The method provided by the present invention allows the surface modified nanoparticles to have better dispersibility in the rubber dispersed phase, and triggers the dynamic crosslinking of the rubber dispersed phase, so that the structural network of the rubber dispersed phase is more perfect, and the morphology of the rubber dispersed phase gradually evolves from an ellipsoid to a long strip, which is more conducive to the propagation of impact energy. At the same time, the particle position is fixed, and a stress concentration point is provided for the dissipation of impact energy, thereby greatly improving the toughness of the composite material. At the same time, the method provided by the present invention allows particles with a higher modulus to equivalently replace part of the rubber dispersed phase of the same volume. At the same time, dynamic crosslinking increases the modulus of the rubber dispersed phase itself, so that the modulus of the PP composite material is greatly improved compared with the elastomer toughened composite material, and the prepared PP composite material has both good strength and toughness.

[0081] The embodiments of the present invention described above do not limit the protection scope of the present invention. Any modification, equivalent substitution and improvement made within the spirit and principle of the present invention shall be included in the protection scope of the claims of the present invention.

Claims

1. A high-strength polypropylene composite material reinforced with an inorganic filler and toughened with an elastomer, characterized in that: The invention comprises the following components in weight percentage: 50%-75% polypropylene, 20%-40% rubber elastic body, 0.5%-20% organic modified inorganic particles, 0-0.1% beta nucleating agent and 0.5%-3% antioxidant.

2. The high-strength polypropylene composite material reinforced with an inorganic filler and toughened with an elastomer according to claim 1, characterized in that: The polypropylene is any one of isotactic copolymer polypropylene, random copolymer polypropylene and high-density polypropylene.

3. The high-strength polypropylene composite material reinforced with an inorganic filler and toughened with an elastomer according to claim 1, characterized in that: The rubber elastomer is at least one of EPDM rubber, EPDM rubber, styrene-butadiene-styrene block copolymer, hydrogenated styrene-butadiene block copolymer, ethylene-octene copolymer, ethylene-octene block copolymer and styrene-ethylene-propylene-styrene block copolymer.

4. The high-strength polypropylene composite material reinforced with an inorganic filler and toughened with an elastomer according to claim 1, characterized in that: The organically modified inorganic particles are at least one of spherical silica, halloysite, silica aerogel, and rod-shaped silica.

5. The high-strength polypropylene composite material reinforced with an inorganic filler and toughened with an elastomer according to claim 4, characterized in that: The method for preparing the organically modified inorganic particles comprises the following steps: S1, dissolving a silane coupling agent in an organic solvent to obtain a modifier solution; S2. Place the inorganic particles in a high temperature mixer and dehydrate at 100-150°C and 200-500 rpm for 20-50 min; S3. Spray the modifier solution prepared in S1 into the high-temperature mixer in S2 in 5-10 times. After each spraying, continue stirring at 100-150° C. and 200-500 rpm for 3-5 minutes. After all spraying is completed, continue stirring for 20-50 minutes.

6. The high-strength polypropylene composite material reinforced with an inorganic filler and toughened with an elastomer according to claim 5, characterized in that: The silane coupling agent is at least one of 3-(2,3-epoxypropyloxy)propyltrimethoxysilane, 3-(2,3-epoxypropyloxy)propyltriethoxysilane, 3-(2,3-epoxypropyloxy)propylmethyldiethoxysilane, 3-(3,4-epoxycyclohexyl)trimethoxysilane, 3-aminopropyltriethoxysilane, methyltrimethoxysilane, phenyltrimethoxysilane, and bis-[γ-(triethoxysilyl)propyl]tetrasulfide.

7. The high-strength polypropylene composite material reinforced with an inorganic filler and toughened with an elastomer according to claim 5, characterized in that: The organic solvent is a 50-100% ethanol aqueous solution; in the modifier solution, the concentration of the silane coupling agent is 1-20 g / ml.

8. The high-strength polypropylene composite material reinforced with an inorganic filler and toughened with an elastomer according to claim 5, characterized in that: The inorganic particles are spherical silica, and the mass ratio of the spherical silica particles to the silane coupling agent is 100:(1-10).

9. The high-strength polypropylene composite material reinforced with an inorganic filler and toughened with an elastomer according to claim 1, characterized in that: The β-nucleating agent is at least one of calcium carbonate, aluminum oxide, anthracene, naphthalene, 2-mercaptobenzimidazole, N,N'-dicycloethylterephthalamide, and TMB-5; the antioxidant is at least one of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol ester, N-isopropyl-N'-phenyl-p-phenylenediamine, 2,2,4-trimethyl-1,2-dihydroquinoline polymer, and 2-mercaptobenzimidazole.

10. A method for preparing a high-strength polypropylene composite material reinforced with an inorganic filler and toughened with an elastomer according to any one of claims 1 to 9, comprising the following steps: S1. Place the organically modified inorganic particles and the rubber elastomer into an internal mixer, and fully blend them at 90-110° C. and 50-80 rpm for 10-15 min to obtain a composite rubber; S2. Put the composite rubber and polypropylene obtained in S1 into an internal mixer, add a β-nucleating agent and an antioxidant, and fully blend at 180-210° C. and 50-80 rpm for 8-12 minutes to obtain a polypropylene composite material.

Citation Information

Patent Citations

  • Inorganic powder and preparation method thereof, and reinforced and toughened polypropylene modified master batch

    CN114539812A

  • Ethylene propylene diene monomer / silicone rubber / polypropylene thermoplastic elastomer and preparation method thereof

    CN117264333A

  • Polyolefin elastomer and application thereof

    CN117511058A

  • Low-gloss high-impact modified polypropylene composite material and preparation method thereof

    CN118290856A

  • Ethylene propylene diene monomer / polypropylene thermoplastic elastomer composition, thermoplastic elastomer material and preparation method and application thereof

    CN118290860A